Exercise-induced circulating microRNA changes in athletes in various training scenarios - Horak, Martin; Zlamal, Filip; Iliev, Robert; Kucera, Jan; Cacek, Jan; Svobodova, Lenka; Hlavonova, Zuzana; Kalina, Tomas; Slaby, Ondrej; Bienertova-Vasku, Julie (PLOS ONE, 2018)
Background The aim of the study was to compare selected extracellular miRNA levels (miR-16, miR-21, miR-93 and miR-222 with the response to 8-week-long explosive strength training (EXPL), hypertrophic strength training (HYP) and high-intensity interval training (HIIT). Methods 30 young male athletes of white European origin (mean age: 22.5 ± 4.06 years) recruited at the Faculty of Sports Studies of Masaryk University were enrolled in this study. The study participants were randomly assigned to three possible training scenarios: EXPL, HYP or HITT and participated in 8-week-long program in given arm. Blood plasma samples were collected at the baseline and at week 5 and 8 and anthropometric and physical activity parameters were measured. Pre- and post-intervention characteristics were compared and participants were further evaluated as responders (RES) or non-responders (NRES). RES/NRES status was established for the following characteristics: 300°/s right leg extension (t300), 60°/s right leg extension (t60), isometric extension (IE), vertical jump, isometric extension of the right leg and body fat percentage (BFP). Results No differences in miRNA levels were apparent between the intervention groups at baseline. No statistically significant prediction role was observed using crude univariate stepwise regression model analysis where RES/NRES status for t300, t60, IE, vertical jump and pFM was used as a dependent variable and miR-21, miR-222, miR-16 and miR-93 levels at baseline were used as independent variables. The baseline levels of miR-93 expressed an independent prediction role for responder status based on isometric extension of the right leg (beta estimate 0.76, 95% CI: -0.01; 1.53, p = 0.052). Discussion The results of the study indicate that 8-week-long explosive strength training, hypertrophic strength training and high-intensity interval training regimens are associated with significant changes in miR-16, mir-21, miR-222 and miR-93 levels compared to a baseline in athletic young men.